Hyaluronan in vocal folds and false vocal folds in patients with recurrent respiratory papillomatosis. (2nd November 2018) - Holm, Anna; Hellman, Urban; Laurent, Claude; Laurell, Göran; Nylander, Karin; Olofsson, Katarina
Abstract: Background: Hyaluronan (HA) is a glycosaminoglycan with viscoelastic properties necessary for vocal fold (VF) vibration and voice production. Changes in HAs molecular mass, possibly related to human papilloma virus, could affect formation/persistence of recurrent respiratory papillomatosis (RRP). Aims/Objective: Describing mass and localization of HA and localization of HA receptor CD44 in VF and false vocal folds (FVF) in RRP. Materials and Methods: Biopsies from VF and FVF from 24 RRP patients. Twelve were studied with histo-/immunohistochemistry for HA and CD44 in epithelium, stroma and RRP lesions. Twelve samples were analyzed for HA molecular mass distribution with gas-phase-electrophoretic-molecular-mobility-analyzer (GEMMA). Results: Three of 23 stains (VF and FVF combined) showed faint HA staining in the epithelium; there was more extensive staining in the stroma. CD44 was present throughout all areas in FVF and VF, it did not concur with HA. GEMMA analysis revealed very high mass HA (vHMHA) with more varying amounts in VF. Conclusions/Significance: HA was mainly distributed in the stroma. CD44 not binding to HA might explain the non-inflammatory response described in RRP. Possibly crosslinked vHMHA was seen in VF and FVF, with more variable amounts in VF samples. Counteracting HA crosslinking could become a treatment option in RRP.